Staying Mobile. A guide to mobility management in ageing societies. - Fiedler, Matthias; Fenton, Bonni (My University, 2011)
Attaining Energy-Efficient Mobility in an Ageing Society (AENEAS) is a project which aims to apply soft measures (e.g. training, individualised travel marketing, awareness raising and events) in five European cities to encourage and enable older people to use alternatives to the private car. The report highlights exemplary programmes and projects that help older citizens to remain active and mobile.
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Radverkehrsförderung; Nachhaltige Mobilität; Mobilitätsmanagement; Demographischer Wandel